2016
DOI: 10.1021/acsomega.6b00163
|View full text |Cite
|
Sign up to set email alerts
|

O-Aryl-Glycoside Ice Recrystallization Inhibitors as Novel Cryoprotectants: A Structure–Function Study

Abstract: Low-molecular-weight ice recrystallization inhibitors (IRIs) are ideal cryoprotectants that control the growth of ice and mitigate cell damage during freezing. Herein, we describe a detailed study correlating the ice recrystallization inhibition activity and the cryopreservation ability with the structure of O-aryl-glycosides. Many effective IRIs are efficient cryoadditives for the freezing of red blood cells (RBCs). One effective cryoadditive did not inhibit ice recrystallization but instead inhibited ice nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 51 publications
2
45
0
Order By: Relevance
“…Additional work showed that supplementing glycerol with milimolar concentrations of O ‐aryl‐ d ‐glycosides 41 , 42 , 43 , 45 , and 47 resulted in increased post‐thaw cell viabilities by 30%–50% and 70%–80% intact RBCs post‐thaw. This demonstrates that cryopreservation is still successful with 15% glycerol (Figure ), which also greatly reduces post‐thaw deglycerolization times . In addition, these IRIs were very effective at protecting RBCs against transient warming effects .…”
Section: Modern Cryobiology and The Use Of “Antifreezes” As Cryoprotementioning
confidence: 83%
See 2 more Smart Citations
“…Additional work showed that supplementing glycerol with milimolar concentrations of O ‐aryl‐ d ‐glycosides 41 , 42 , 43 , 45 , and 47 resulted in increased post‐thaw cell viabilities by 30%–50% and 70%–80% intact RBCs post‐thaw. This demonstrates that cryopreservation is still successful with 15% glycerol (Figure ), which also greatly reduces post‐thaw deglycerolization times . In addition, these IRIs were very effective at protecting RBCs against transient warming effects .…”
Section: Modern Cryobiology and The Use Of “Antifreezes” As Cryoprotementioning
confidence: 83%
“…Para ‐methoxyphenyl‐β‐ d ‐glycosides (PMP) were the first in their class to be tested as inhibitors for ice recrystallization, and unlike previous observations, the glucose derivative β‐PMP‐Glc ( 41 ) was significantly more active than its galactose ( 39 ) and mannose ( 40 ) derivative . Several para‐substituted derivatives of d ‐glucose, d ‐galactose, and d ‐mannose were also evaluated for IRI activity . The results suggested that electronic effects do not influence the IRI activity of O ‐aryl‐glycosides in any predictable fashion as strongly electron withdrawing substituents (–F, –Br, –Cl, –CF 3 ) resulted in moderate to high activity, but para‐substitution with –NO 2 resulted in minimal IRI activity.…”
Section: Inhibiting Ice Recrystallization Using Small Moleculesmentioning
confidence: 96%
See 1 more Smart Citation
“…11,[14][15][16][17][18] The Ben laboratory has been designing and synthesizing small molecule IRIs and has demonstrated their advantages in many in vitro cellular systems. 4,[19][20][21][22][23] The structure of aldonamide-derived IRI is shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…Carbohydrates alone have some weak IRI, with the hypothesis that their degree of hydration correlates with activity, but whether this relationship holds when attached to the AFGP backbone remains unknown 44 , 49 . Ben and co-workers were the first to report the synthesis of low molecular weight carbohydrate derived small molecules possessing IRI activity 46 , 49 , 50 . Inspired by the obvious presentation of hydrophobic faces in AF(G)Ps, (Fig.…”
Section: Small Molecule and Peptide Based Mimicsmentioning
confidence: 99%